Assessing the "Angola Model" finance: The case of Angola - Roxo, Frederico Luís Cambóias (2022)
China’s increasing role as a financier to Africa has been extensively discussed in the last decades. In this context, Angola has come to see China as an important developmental partner, owing to the country’s reliance on Chinese financing to support development projects. Key to China’s developmental lending strategy in Africa is a model of financing whereby loans are repaid by the borrowers with commodities. This form of finance became known as the “Angola Model” and has been widely used in Angola, where the country leverages on its vast oil reserves to secure infrastructure developing funding. This research aims to assess the “Angola Model” finance in Angola, exploring its main features and implications on the China-Angola relation. Through a quantitative study conducted on data sourced from a database on China’s lending and additional information on Angola’s external statistical data, the results identify the loans’ terms and distribution in Angola and suggest an influence of the “Angola Model” finance on the deepening of the China-Angola commercial and financial relations.